PELATIHAN PENGGUNAAN DROPBOX UNTUK MANAJEMEN IKLAN KORAN BANJARMASIN POST GROUP PADA PT BANJARMASIN KARYA UTAMA - Nur Alamsyah; Muhammad Rasyidan (Universitas Islam kalimantan MAB, 2017)
In the process of mounting an ad to be aired or published, an advertisement must be designed in advance as you wish installer and adapted to the size and content of the material you want to advertise. This time the results of advertising design sent from the office of PT BKU to Banjarmasin Post office (section Advertising Production) via email. Sending files advertising design via email often experience problems that the size of the design files exceed the maximum limit on the delivery of email which is only 25 MB only, while the size of the ad design can sometimes be up to 75 MB and even 500 MB, because if the size is too converted (under 25MB), the results of design display can be blurred or broken, so they can let advertisers. Therefore, to overcome the above problems with the development of IT is now no such thing as Cloud Computing, which is an online file storage in the form of documents, images or video. DropBox is storage (storage) offers 2 GB of storage space for free. Unlike other file hosting, DropBox advantages is that it can be synchronized directly on the computer that we use (PC or Handphone), so that we can access the files that we save wherever we are, even while offline.